Associations Between Maternal Dietary Choline Intake During Pregnancy and Developmental Outcomes in Toddlers. (29th May 2020) - Fawcett, Kindann; Sims, Clark; Gaitliff, Rosemary; McCorkle, Ginger; Bellando, Jayne; Phelps, Joshua; Andres, Aline
Abstract: Objectives: Recent studies indicate that adequate choline intake in pregnancy results in increased cognitive, motor, language, and behavioral scores in toddlers. The objective was to examine the relationship between maternal choline intake during pregnancy and children's developmental scores during the first two years of life. Methods: De-identified secondary data from a longitudinal study (NCT#0, 328, 1851) involving women with normal weight, overweight, and class I obesity (BMI:18.5- 35 kg/m, 2 N = 251) during pregnancy and their children were analyzed using Pearson's correlations and linear models. Dietary choline intake was obtained by analyzing 3-day food records at each trimester using the Nutrient Data System for Research. Cognitive, motor, language, social emotional, and adaptive behavioral scores at 1 and 2 years of age were derived from the administration of the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III). Results: Adequate Intake (AI) for average maternal choline intake was only met by 4 of the 251 participants. Mean intake of maternal choline during pregnancy (281 mg/day) was significantly lower than the AI level of pregnant women (AI = 450 mg/day). Mean standard scores for Bayley-III domains were all within the normal range (102 for cognitive, 101 for motor, 96 for language, 109 for social-emotional, and 94 for adaptive behavior). Higher maternal choline intake yielded lower adaptive development at 12 months of age ( P < 0.001) and 24 months of age ( P  = 0.044) after adjusting for gestational age and birthweight. There were no associations between maternal choline intake and cognitive, motor, language and social-emotional scores at both ages. Conclusions: In this cohort from Arkansas, maternal choline intake was not associated with four of the children's neurodevelopmental outcomes. Maternal Choline intake was negatively associated with the self-reported adaptive behavior scope, which is in contrast to previously published literature. It is important to note that infant development scores were all within normal range despite 98% of women not meeting the AI recommendations for dietary choline during pregnancy. Analyses of choline serum concentration from this cohort is underway to confirm these results. Funding Sources: USDA ARS Project # 6026–51, 000-012–06S, NIH R01 DK107516.